Structural determinants within Pbx1 that mediate cooperative DNA binding with pentapeptide-containing Hox proteins: proposal for a model of a Pbx1-Hox-DNA complex. - Lu, Q (1996)
Genetic studies have identified a family of divergent homeodomain proteins, including the human protooncoprotein Pbx1 and its drosophila homolog extradenticle (Exd), which function as cofactors with a subset of Hox and HOM-C proteins, and are essential for specific target gene expression. Pbx1/Exd binds DNA elements cooperatively with a large subset of Hox/HOM-C proteins containing a conserved pentapeptide motif, usually YPWMR, located just N terminally to their homeodomains. The pentapeptide is essential for cooperative DNA binding with Pbx1. In this study, we identify structural determinants of Pbx1 that are required for cooperative DNA binding with the pentapeptide-containing Hox protein HoxA5. We demonstrate that the homeodomain of Pbx1 contains a surface that binds the pentapeptide motif and that the Pbx1 homeodomain is sufficient for cooperative DNA binding with a Hox protein. A sequence immediately C terminal to the Pbx1 homeodomain, which is highly conserved in Pbx2 and Pbx3 and predicted to form an alpha-helix, enhances monomeric DNA binding by Pbx1 and also contributes to maximal cooperativity with Hox proteins. Binding studies with chimeric HoxA5-Pbx1 fusion proteins suggest that the homeodomains of Pbx1 and HoxA5 are docked on the representative element, TTGATTGAT, in tandem, with Pbx1 recognizing the 5' TTGAT core motif and the Hox protein recognizing the 3' TGAT core. The proposed binding orientation permits Hox proteins to exhibit further binding specificity on the basis of the identity of the four residues 3' to their core binding motif.